PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL - Yoyon Moheri; Dista Amalia Arifah (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2015)
This study aims to analyzed budget participation influenced toward managerial performance with management costing knowledge and motivation as moderating variable. The population included was manufacture companies in Semarang City. Sampling using a purposive sampling method and obtained 84 samples that meet the criteria and free from outliers. The data used in this study is primary data, questioners for managerial level. Multiple Regression was used as analysis technique. The result showed that only motivation was rejected, while budget participation and management costing knowledge hypothesis was accepted.Keywords : budget participation, management costing knowledge, motivation